Peningkatan Mutu Proses Pembelajaran Berorientasi Pada Aktivitas Siswa - Krowin, Martinus M. (Universitas 17 Agustus 1945 Samarinda, 2016)
One of the national problem in our education nowdays is the low quality of it. It is, therefore, there are many efforts by the goverment to improit by to improve the tools, instrument’s, human resources curriculum, budget and other else. In this research is willing to know about the improvement of the quality of the student’s activity the location in manado in 2016. The methods is qualitative one. The results of the research is that by the gift of the portain for the student’s they will be given the opportunity to strengthen the cognitive, effective and psicomotoric domain. In cognitive domain they will enlarge the knowledge, creativity, inovation and change the social action to sinergic effect, and the psicomotoric they are able to practice the knowladge into action. The suggestions are (1) the student’s have to be en courage to enrich the science and to be intellectual person (2) the student’s have to suport to be good attitude (3) the student’s have to motivate to practice in the field.